COGNITIVE LEARNING STRATEGY THROUGH NUMBER GAMES USING BOTTLE CAPS FOR CHILDREN AGED 4–5 YEARS AT TK ALAM PURWAKARTA IN THE 2025/2026 ACADEMIC YEAR - Inayatul Azizah, Siti Maemunah; Syahidin, Samin (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study was motivated by the importance of stimulating cognitive aspects in early childhood as one of the foundations for intellectual development and logical thinking skills. Observations at Alam Purwakarta Kindergarten showed that some 4-5-year-old children still had difficulty recognizing numbers, counting objects, and grouping objects according to the correct numbers. This is thought to be due to conventional teaching methods that do not actively involve children. Therefore, this study examines the effectiveness of cognitive learning strategies through number games based on bottle caps, which are designed to suit the characteristics of early childhood, namely learning through play. Based on these results, it can be concluded that cognitive learning strategies through bottle cap number games are very effective in improving the cognitive abilities of early childhood. This medium is not only simple and environmentally friendly, but also capable of creating a fun, interactive, and contextual learning atmosphere in line with the world of children. The application of this strategy not only helps children understand number concepts concretely but also fosters self-confidence, active engagement, and logical thinking skills, which are important foundations for the next stage of education.